Identification of two novel ferroptosis-associated targets in sepsis-induced cardiac injury: Hmox1 and Slc7a11 - Xu, Yushun; Bu, Gang (Frontiers in Cardiovascular Medicine, 2023)
Purpose: Sepsis-induced cardiac injury is a severe complication of sepsis and has a high mortality. Recent research has implicated ferroptosis as a contributing factor to myocardial cell death. This study was aimed at finding novel ferroptosis-associated targets in sepsis-induced cardiac injury. Methods and results: In our study, a total of two GEO datasets (GSE185754 and GSE171546) were obtained for bioinformatics analysis. GSEA enrichment analysis demonstrated that ferroptosis pathway Z-score rapidly increased in the first 24 hours and decreased gradually in the following 24-72 hours. Fuzzy analysis was then used to obtain distinct clusters of temporal patterns and find genes in cluster 4 that exhibited the same trend with ferroptosis progression during the time points. After intersecting the differentially expressed genes (DEGs), genes in cluster 4 and ferroptosis-related genes (FRGs), three ferroptosis-associated targets were finally selected: Ptgs2, Hmox1 and Slc7a11. While Ptgs2 has been previously reported to be involved in the regulation of septic cardiomyopathy, this study is the first to demonstrate that downregulation of Hmox1 and Slc7a11 can alleviated the ferroptosis in sepsis-induced cardiac injury. Conclusion: This study reports Hmox1 and Slc7a11 as ferroptosis-associated targets in sepsis-induced cardiac injury, and both of them may become key therapeutic and diagnostic targets for this complication in the future.